PUBLIC ADMINISTRATION MECHANISMS IN THE IMPLEMENTATION OF LOCAL AND REGIONAL PROGRAMS IN THE CONTEXT OF DECENTRALIZATION OF POWER - HAYDUK, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a thorough theoretical and applied study of public management mechanisms for the implementation of local and regional programs in the context of decentralization of power in Ukraine. It is substantiated that the transformation processes taking place in the field of public management in the context of decentralization necessitate a rethinking of traditional approaches to the formation, planning and implementation of development policies at the local and regional levels. Special emphasis is placed on the essence, structure and functioning of public management mechanisms that ensure the effective implementation of territorial development programs and projects. The content of the program-project approach is revealed as a key tool of modern strategic management, which allows combining target benchmarks with resource provision tools and performance assessment indicators. The work systematizes the main components of public management mechanisms, in particular institutional, regulatory, information-analytical, financial-economic, personnel and technological. Based on the analysis of scientific sources, modern legislative framework and examples from the practice of local government, it was established that the key factors for the successful implementation of local programs are well-established interagency cooperation, a sufficient level of budgetary autonomy of communities, professional capacity of management personnel, transparency of decision-making procedures, as well as digital transformation of management processes. The main challenges that complicate the effective implementation of public administration in the regions are identified: uneven development of territorial communities, staff shortage, fragmentation of regulatory and legal support, imperfection of monitoring and evaluation mechanisms. The feasibility of a comprehensive approach to the modernization of management mechanisms with a focus on strengthening the capacity of communities, developing digital infrastructure, improving the strategic planning system and increasing citizen participation in decision-making is substantiated. The importance of implementing international project management practices adapted to Ukrainian realities is also emphasized.
Keywords: public administration; decentralization; local self-government; regional development; territorial communities; program-project approach; strategic planning; project management; digital governance; institutional capacity; community participation